Split nitrogen sources effects on nitrogen use efficiency, yield and seed quality of safflower (Carthamus tinctorius L.) - Moradi Talebbeigi, Reza; Kazemeini, Seyed Abdolreza; Ghadiri, Hossein; Edalat, Mohsen (Italian Journal of Agronomy, 2018)
The effects of nitrogen (N) on crop yields have historically been assessed with field trials, but selection and use of the best sources and optimal timing N applications have a significant role in realizing the maximum potential of oilseeds quality and quantity. This study was conducted to determine the combine effects of N sources [ammonium nitrate (AN), ammonium sulphate (AS), sulphur coated urea (SCU), and urea (U)] and split N fertilisation [(1/4,3/4,0), (1/3,1/3,1/3), (1/2,1/2,0), and (1/3,2/3,0)] on safflower (Carthamus tinctorius L.) some growth characters, yield and seed quality, and N use efficiency based on a split plot design with three replications at the experimental research station, Shiraz University in 2015 and 2016. The highest safflower dry matter (5140.93 kg ha–1), seed yield (3303.52 kg ha–1) and protein yield (694.95 kg ha–1) were achieved with the application of AN fertiliser in a split pattern of 1/2,1/2,0 (applying half of the N at sowing time and the rest at stem elongation), while the highest oil yield (753.09 kg ha– 1) was observed by U fertiliser and similar split pattern. Applying AN fertiliser and split patterns of 1/3,2/3,0 (applying one third of the N at sowing and two thirds of the N at stem elongation) and 1/4,3/4,0 (applying one quarter of the N at sowing and three quarters at stem elongation) maximised safflower N uptake efficiency (NUpE) (0.78 kg kg–1). However, the highest N utilisation efficiency (NUtE) (43.70 kg kg–1) was obtained when AN fertiliser in a split pattern of 1/2,1/2,0 was applied. On the contrary, applying AS and SCU fertilisers was less effective on safflower performance by all split patterns. It is concluded that applying AN fertiliser in a split pattern of 1/3,2/3,0 and or U fertiliser in a split pattern of 1/2,1/2,0 not only enhanced safflower growth, yield and seed quality improved, but also increased the N use efficiency of safflower.